Relevansi Nilai-Nilai Piagam Madinah dan Prinsip Demokrasi di Indonesia - Muhammad Rusydan Abdul Hadi; Tazkiya Humanissa; Elvaretta Munar; Muhammad Parhan (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
The Medina Charter is the first written constitution initiated by the Prophet Muhammad SAW with the people of Medina. The background of the people of Medina is very diverse so that this constitution plays an important role in regulating and realizing unity and peace in Medina. This is certainly in line with Indonesia's very diverse conditions. Indonesia also uses a democratic system in its government. The values contained in the Medina Charter are in line with the concept of democracy although not directly. The Medina Charter has the same principles in the implementation of democracy proposed by David Held. This research method uses a qualitative approach with a type of historical research and literature study instruments to find information. The findings are that the values contained in the Medina Charter have relevance to the principles of democracy such as the principles of freedom, equality, justice, tolerance, openness, participation and responsibility. This research aims to understand the democratic values in the Medina Charter so that it can be used as a reference in facing challenges and improving democracy in Indonesia in modern times. The novelty of this research discusses in detail the seven principles of democracy in the Medina Charter and Democracy in Indonesia.